T&T clark handbook of election - Driel, Edwin Chr. van (t&tclark, 2026)
"Offering not only state-of-the-art introductions from Biblical, historical, and constructive theologians, this volume also fosters an inter-disciplinary and cross-confessional conversation, reclaiming the idea of election as a central notion for any retelling of the biblical narrative. Several essays explore the variety of ways in which election is spoken about in the Scripture, drawing on research from the last twenty years that offers a more sophisticated framework than the traditionally theological categories of "elect" and "reject". The historical part of the volume covers new analyses of Medieval and post-Reformation Catholic and Protestant debates on predestination, while the book's constructive part contributes to contemporary conversations on the relationship between Trinity, Christology, and election, the development of a post-supersessionist understanding of Israel's chosenness, as well as voices from contextual struggles in South America, Palestine, and South Africa."--